Highly efficient few-cycle laser wakefield electron accelerator. (11th May 2021) - Papp, Daniel; Lécz, Zsolt; Kamperidis, Christos; Hafz, Nasr A M
Abstract: A significant part of the laser wakefield acceleration (LWFA) research effort focuses on studying high-energy, quasi-monoenergetic electron beams. For other applications, such as the production and application of intense betatron x-ray radiation, Bremsstrahlung γ -rays and positron beams, the beam's spectral quality is secondary to the number of electrons produced. This work discusses 3D particle-in-cell simulations of a highly efficient LWFA acceleration process, generating a broad spectrum of electrons, driven by a 12 TW few-cycle laser on high-density gas targets. In some cases, laser absorption in plasma exceeds 80%, and up to 27% of the driving laser energy is transferred to electrons over 20 MeV leaving the plasma. We also observe a deceleration of the accelerated beam at the plasma downramp and plasma exit, which arises from transitioning from laser-driven to beam-dominated wake, and also from the induced axial electric field. This effect is similar to magnetic vortex acceleration, where the induced axial electric field, instead of accelerating plasma ions, would slow down the opposite-charged electron beam and also a strong return current and backward electron beam.